A Manual for Writers of Term Papers, Theses, and Dissertations / Kate L Turabian, Bonnie Birtwistle Honigsblum - Turabian, Kate L
This guide to the methods, materials, and technologies that are available to help writers of research papers includes a chapter on computer usage, information on the preparation and presentation of tables, and extensive examples.